Noncommunicable disease-attributable medical expenditures, household financial stress and impoverishment in Bangladesh - Biplab Kumar Datta; Muhammad Jami Husain; Muhammad Mudabbir Husain; Deliana Kostova (Elsevier, 2018)
Background: Treatment of noncommunicable diseases (NCDs) in low-income countries can entail large out-of-pocket (OOP) medical expenditures, which can increase the likelihood of household impoverishment and perpetuate the poverty cycle. This paper studies the implications of NCDs on household medical expenditure, household financial stress (e.g. selling assets or borrowing for treatment financing), catastrophic OOP expenditure, and impoverishment in Bangladesh. Methods: We used self-reported health status and household expenditure survey data from 12,240 households in Bangladesh. NCD-afflicted households were defined by presence of at least one of the following conditions within the household - heart disease, hypertension, asthma, diabetes, cancer, or kidney disease. Using linear regression models, we examined whether NCD households incur more medical expenditures, allocate a larger budget share on medical expenditures, and have greater probability of experiencing catastrophic medical expenditure or financial stress from OOP spending than non-NCD households. Finally, using survey weights, we extrapolated how NCD-attributable medical expenditure can result in impoverishment and downward movement in net consumption status at the population level. Results: NCD-afflicted households allocate a greater share of household expenditures for medical care than households without NCDs, and their probability of incurring catastrophic medical expenditure is higher by 6.7 percentage points compared to the households with no reported conditions. NCD households are 85% more likely to sell assets or borrow from informal sources to finance treatment cost. Household spending on NCD care is estimated to account for the impoverishment of 0.66 million persons in Bangladesh in 2010, and for reducing the net consumption status of 7.63 million persons on both sides of the poverty line after accounting for NCD-related OOP expenditures. Conclusion: NCD-related household medical expenditure is associated with experiencing financial distress and aggravating poverty in Bangladesh.